Curcumin loading and colon release of pectin gel beads: Effect of different de-esterification method. (30th September 2022) - Cai, Ran; Pan, Siyu; Li, Ruoxuan; Xu, Xiaoyun; Pan, Siyi; Liu, Fengxia
Graphical abstract: Highlights: Low methoxyl pectin (LMP) was obtained by different de-esterification methods. High hydrostatic pressure (HHP) showed the advantage in pectin de-esterification. Curcumin was loaded well in LMP calcium gel beads with improved stability. HHP-LMP had the highest branching extent of RG-I and lowest linear degree. HHP-LMP beads had better loading performance and released in colon more quickly. Abstract: Low methoxyl citrus pectin (LMP) de-esterified from high hydrostatic pressure assisted enzymatic (HHP-pectin) and two other traditional methods was characterized, and curcumin-pectin calcium gel beads were prepared to study curcumin-loading and colon-targeted delivery abilities. It was found there was no significant difference among different LMP on amorphous structure, while significantly higher Rha/GalA ratio of HHP-pectin indicated higher rhamnogalacturonan Ⅰ (RG-I) proportion and branching extent. Curcumin was well embedded in LMP beads with improved stability. HHP-pectin beads showed significantly higher hardness, chewiness and encapsulation efficiency, while lower swelling ratio. Moreover, in vitro simulated digestion showed gel beads can deliver curcumin to colon and inhibit premature release. HHP-pectin beads could release curcumin more quickly in colon, probably because of differences on texture properties, which may be depended on molecular structure. Thus, LMP especially HHP-pectin calcium gel as colon-targeted delivery system for curcumin may have potential application in function food and drug delivery.